Efficacy of dimethyl disulfide and metam sodium combinations for the control of nutsedge species. (August 2018) - Stevens, Mary; Freeman, Joshua
Abstract: Dimethyl disulfide (DMDS) is a methyl bromide alternative with good to excellent nutsedge control when mixed with chloropicrin (Pic). Combining fumigants is a common practice to improve pest control spectrum, however, the use of Pic is restricted in some countries. In order to determine the legitimacy of replacing Pic in DMDS:Pic combinations, a low and high rate of metam sodium (MNa) was used alone and in combination with DMDS and were compared to a single rate of DMDS alone and in combination with Pic to determine their efficacy against nutsedge species and impact on muskmelon yield. All DMDS combinations resulted in lesser nutsedge populations than MNa alone and the non-treated control. MNa applied alone, even under totally impermeable film, was not enough to control nutsedge species. DMDS combinations also provided greater nutsedge control than DMDS applied alone at seasons end. Furthermore, MNa applied concurrently with DMDS may have the potential to replace DMDS:Pic combinations without losing efficacy on nutsedge species in geographies where the use of Pic is restricted. Highlights: DMDS:MNa resulted in significantly lower nutsedge density than the control. DMDS:MNa resulted in significantly higher yield than MNA applied alone. Results indicate that MNa has the potential to replace Pic in DMDS combinations.